Pengaruh Overlapped Audit Committee terhadap Pengungkapan Key Audit Matters di Indonesia - Dinata, Ikkral; Cheisviyanny, Charoline (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to determine the overlapping relationship between the Audit Committees influencing the disclosure of Key Audit Matters (KAMs) in Indonesia. This study uses quantitative research methods with hypotheses. Data collection techniques using non-participant observation. Research on KAMs is very interesting to do because there have been several studies that have investigated the factors that influence KAMs for developed countries, but there has been no research that has tried to analyze this in Indonesia. Based on the results of the study, it was found that the hypothesis (H1) is appropriate and it can be concluded that the level of overlap between members of the Audit Committee has a positive relationship with the level of disclosure of KAMs in the company's financial statements. This can be seen from the partial test results with a significance value of 0.0290 (0.290 <0.05) and a positive β coefficient of 0.231. This shows that the greater the level of concurrent positions in the Audit Committee owned by the company, the higher the number of KAMs disclosed by the company. For further researchers, they can expand the population and sample, not only limited to financial sector companies on the IDX in 2022, then compare how the company characteristics influence before the implementation of the ISA 701 Key Audit Matters regulations and after the implementation of ISA 701 Key Audit Matters in Indonesia, and can add the use of other variables that can affect the disclosure of KAMs.